Planning your speech (Centron Educational Films, 1979)
A look at the process of planning a speech, beginning with an invitation to speak and then illustrating how the speaker prepares for the occasion. Much of the film involves an interaction between the speaker and his "common sense". The introduction to the speech, illustrative materials, and audience awareness are discussed. From the Art of communication series.